Find grant funding now! : the five-step prosperity process for entrepreneurs and business - Aubrey, Sarah Beth. (Hoboken, New Jersey : Wiley, 2014)
'This book is built around the Five-Step Prosperity Process Aubrey uses for her clients every day. Other features will include sample forms, such as Letters of Intent, grant searching checklists, budgets, narrative formation, sample merit review, checklist for the top five feasibility points, 30 and 60 day grant project management plans, and very importantly, the customized Grant Readiness Assessment Tool. The book will have sidebars with quotes and resources and a custom illustrated schematic of the Five Step Prosperity Process that is highlighted in each chapter to show where at in the process as they progress through the book. It will also include snap tags in each chapter that link to videos and excerpts of additional content. There are books on grant writing and there are books on business, there are even books that tell you how to start a grant writing business. This book is about how and when you could use grants to get cash to start or expand your business. This is the book the small business financial market has been missing!'--
Includes index.
Print version record and CIP data provided by publisher.
Keywords: New business enterprises -- Finance; Small business -- Finance; Grants-in-aid.; BUSINESS & ECONOMICS -- Nonprofit Organizations & Charities; Grants-in-aid.; New business enterprises -- Finance; Small business -- Finance; Electronic books; Electronic books